PENINGKATAN KEMAMPUAN DALAM PEMAHAMAN KONSEP MENGGUNAKAN PENDEKATAN KONTEKSTUAL SISWA KELAS X PENGOLAHAN HASIL PERTANIAN (PHP) SEMESTER 1 - Sudjadi, Sudjadi (Jurnal Cakrawala Pendidikan, 2008)
AbstractThis study aims to improve students learning outcomes in terms of studentsconceptualization ability, students understanding of the concepts of Plant Tissueand Plant Morphology, effect size of learning, and students responses to learningthat applies the contextual approach emphasizing students role in learning. Thisstudy was an action research study involving Year X students of PHP SMKN 1Pandak, Bantul, Yogyakarta. This study consisted of Cycle I with the competencystandard of Plant Tissue and Cycle II with the competency standard of PlantMorphology. The data on the conceptualization ability were collected throughobservations and a written test, those on understanding of concepts through awritten test, values of the effect size and students reflection, and those on studentsresponses to learning through a student questionnaire. The data were analyzedusing the descriptive technique. The results of the study showed that, based onobservations, the students conceptualization ability improved in all aspects,including labeling objects, recording data, interpreting data, drawing conclusions,and treating objects. In the conceptualization ability obtained from the written test,more than 75% of the students had correct answers. The students understanding ofthe concepts of Plant Tissue and Plant Morphology in the aspects of differentiating,explaining, giving examples and drawing conclusions improved. The values of theeffect size describing the learning progress were relatively high, namely 2.58 inCycle I and 4.87 in Cycle II. The students responses to learning were good,indicated by expressions such as useful, expected, free to express ideas,challenging, satisfactory, making autonomous, enjoyable, and having enough time.Keywords: concept understanding, contextual approach